Gerenciamento dos resíduos no processo de fundição: uma análise crítica - Adilson Raimundo de Souza (2004)
The foundry industry in Brazil plays an important role in the developing process of the country. It constitutes a part of the countrys economy with significant turnover and working mass potential. Foundries, like any other industries, transform raw materials into commercial goods required by society. Often, during these processes, considerable severe damages can be imposed upon the natural ecosystems. The Brazilian foundry industry has, to now, become a great solid waste generator mainly sand products whose management has turned out to be a problem of great concern to the country. Hence the purpose of the present work aimed at collecting data regarding the State of the Art as far as the environmental management in the Brazilian foundry industry is concerned. Thus, waste generation and reutilization avenues were studied in order to find out real backfill discharge possibilities looking to minimize environmental degradation. Well-know abroad foundries were also studied during this work in order to determine whether transfer of environmental management technologies maw be a feasible task. The results of data collection applied to Brazilian foundries reveal very small investmentsin environmental issues and these exist mainly due to law adjusting needs. At the same time, foundry industries, although sensible to this matter, tend to justify lack of action due to financial difficulties.